Food insecurity and low CD4 count among HIV-infected people: a systematic review and meta-analysis. Issue 12 (1st December 2016) - Aibibula, Wusiman; Cox, Joseph; Hamelin, Anne-Marie; Mamiya, Hiroshi; Klein, Marina B; Brassard, Paul
ABSTRACT: Food insecurity is defined as a limited or uncertain ability to acquire acceptable foods in socially acceptable ways, or limited or uncertain availability of nutritionally adequate and safe foods. While effective antiretroviral treatment can significantly increase CD4 counts in the majority of patients, there are certain populations who remain at relatively low CD4 count levels. Factors possibly associated with poor CD4 recovery have been extensively studied, but the association between food insecurity and low CD4 count is inconsistent in the literature. The objective is to systematically review published literature to determine the association between food insecurity and CD4 count among HIV-infected people. PubMed, Web of Science, ProQuest ABI/INFORM Complete, Ovid Medline and EMBASE Classic, plus bibliographies of relevant studies were systematically searched up to May 2015, where the earliest database coverage started from 1900. Studies that quantitatively assessed the association between food insecurity and CD4 count among HIV-infected people were eligible for inclusion. Study results were summarized using random effects model. A total of 2093 articles were identified through electronic database search and manual bibliographic search, of which 8 studies included in this meta-analysis. Food insecure people had 1.32 times greater odds of having lower CD4 counts compared to food secure people (OR = 1.32, 95% CI: 1.15–1.53) and food insecure people had on average 91 fewer CD4 cells/µl compared to their food secure counterparts (mean difference = −91.09, 95% CI: −156.16, −26.02). Food insecurity could be a potential barrier to immune recovery as measured by CD4 counts among HIV-infected people.